Morphological properties of Al-doped ZnO nano/microstructures. (March 2016) - Kim, Kyung Ho; Umakoshi, Tomoyuki; Abe, Yoshio; Kawamura, Midori; Kiba, Takayuki
Abstract: We discussed the morphological properties of Al-doped zinc oxide (Al–ZnO) microrods grown on a ZnO seed layer and precipitation particles and compared them with undoped ZnO samples. The ZnO nanorods grown on a ZnO seed layer were dense and perpendicular to the surface of the substrate, i.e., fluorine-doped tin oxide (FTO). In contrast the Al–ZnO grew as larger microrods, and the rods were sparsely and obliquely arranged. Precipitation particles synthesized in the ZnO solution through homogeneous nucleation had flower-like structures assembled from the rods and individual rods with lengths of several micrometers. Al–ZnO precipitation particles consisted of rods with length of several micrometers and hexagonal nanoplates. Fourier transform infrared (FTIR) analysis results showed that the rods and precipitation particles had the good chemical properties of ZnO. Both size and morphology of the rods could be effectively controlled by adding aluminum nitrate (Al(NO3 )3 ) as dopant in the ZnO rod solution. Highlights: Well-aligned ZnO nanorods with a high density were grown on the ZnO seed layer. The randomly oriented Al–ZnO microrods were observed because of few nuclei sites. Flower-like structures and single rods were found in the ZnO precipitation particles. Al–ZnO precipitation particles consisted of micro-size rods and hexagonal nanoplates.